2014
DOI: 10.1111/asj.12240
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a natural feed additive (Macleaya cordata), containing sanguinarine, on the performance and health status of weaning pigs

Abstract: The aim of this study was to investigate the efficacy of Sangrovit(®) , a plant-derived feed additive, given throughout the nursery stage via feed at 15 ppm and 50 ppm, on the health status and performance of weaners against negative controls. In a 900-sow farrow-to-finish farm, a total of 864 piglets were divided into three groups: (i) negative controls (NC); (ii) Sang 15: same feed as NCs, plus 15 g Sangrovit(®) /t of feed; (iii) Sang 50: same feed as NCs plus 50 g Sangrovit(®) /t of feed. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 24 publications
3
64
0
4
Order By: Relevance
“…found that supplementation of 50 mg/kg Sangrovit® (containing 0.75 mg/kg sanguinarine) in the feed significantly increased feed consumption and feed conversion ratio in six-week-old piglets [2]. The performance discrepancy between different studies may be attributed to different sample size, difficulty in showing significant growth changes in short periods or growth variation between different swine breeds, as [13] reported that Sangrovit® exerted a significant effect on body weight gain and feed conversion ratio in two out of four experiment conducted on swine of different breeds and ages, but there were no effects on growth performance in the other two experiments.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…found that supplementation of 50 mg/kg Sangrovit® (containing 0.75 mg/kg sanguinarine) in the feed significantly increased feed consumption and feed conversion ratio in six-week-old piglets [2]. The performance discrepancy between different studies may be attributed to different sample size, difficulty in showing significant growth changes in short periods or growth variation between different swine breeds, as [13] reported that Sangrovit® exerted a significant effect on body weight gain and feed conversion ratio in two out of four experiment conducted on swine of different breeds and ages, but there were no effects on growth performance in the other two experiments.…”
Section: Resultsmentioning
confidence: 98%
“…M. cordata has been reported to contain considerable amounts of isoquinoline alkaloids, mainly sanguinarine and chelerythrine [1]. Sanguinarine and chelerythrine are bitter in taste and have the potential use as flavoring components to increase the feed intake in farm animals [2]. Swine is one of the most important livestock that provides more than one third of the meat production in the world [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus it appears that MCE (and other growth promoters) inhibit inflammation in vitro as well as in vivo [10] [21]. Inflammation is known to reduce growth (through inappetance and muscle catabolism), which explains why effective growth promoters must be inhibitors of inflammatory responses, thus sparing energy for growth [2].…”
Section: Discussionmentioning
confidence: 99%